Reservoir compartmentalization assessed with fluid compositional data - Smalley,PC; England,WA (SPE Reservoir Engineering Society of Petroleum Engineers, 1994)
Fluid composition is a valuable addition to the battery of 'static' data available during reservoir appraisal than can be used to predict the dynamic behavior of the reservoir later in field life. This is because fluid data are not truly static; natural fluid mixing is a dynamic process that occurs over a long (geologic) time scale. Oil compositional differences, especially those that parallel changes in density, should be mixed rapidly by convection; their preservation indicates barriers to fluid flow. Water variations, now measurable on conventional core samples by use of residual salt analysis (RSA), help identify barriers to vertical fluid flow in oil and water legs.